2018
DOI: 10.1111/pai.12847
|View full text |Cite
|
Sign up to set email alerts
|

Side effects during subcutaneous immunotherapy in children with allergic diseases

Abstract: Subcutaneous immunotherapy is a safe form of therapy in pediatric patients, with similar rates of local side effects compared to adult patients and low rates of severe systemic side effects. However, local and systemic reactions occurring later than 30 minutes after injection were observed more often than expected, which makes it essential to be attentive on behalf of pediatricians, patients, and parents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 16 publications
(34 reference statements)
4
17
0
Order By: Relevance
“…Anaphylaxis to RCM occurred in 1.2% of our patients, percentage similar to that observed by others [11,25,38].Severe reactions attributed to RCM have been decreasing due to the fact that, currently, high osmolality ionic formulations are no longer used [38]. In this registry, anaphylaxis during allergen-specific immunotherapy was a rare event, lower than in other case-series [8,16,22,37], confirming the current safety of this treatment [41,42]. Idiopathic anaphylaxis may account for up to 20% of all cases of anaphylaxis [1,23,43];however, this diagnosis of exclusion was rare (2%) in our registry.…”
Section: Discussionsupporting
confidence: 89%
“…Anaphylaxis to RCM occurred in 1.2% of our patients, percentage similar to that observed by others [11,25,38].Severe reactions attributed to RCM have been decreasing due to the fact that, currently, high osmolality ionic formulations are no longer used [38]. In this registry, anaphylaxis during allergen-specific immunotherapy was a rare event, lower than in other case-series [8,16,22,37], confirming the current safety of this treatment [41,42]. Idiopathic anaphylaxis may account for up to 20% of all cases of anaphylaxis [1,23,43];however, this diagnosis of exclusion was rare (2%) in our registry.…”
Section: Discussionsupporting
confidence: 89%
“…In some Chinese patients' studies, SRs occurred in 12.26-18.49% of patients and 0.72-3.28% of injections in children. We also found the majority of the SRs were grade 1 and grade 2 reactions, which was consistent with previous studies [31,32]. Only 2 /91 (4.55%) patients experienced grade 3 reactions within 30 min after injection and responded well to rescue medication, no patient had grade 4 or grade 5 reaction.…”
Section: Discussionsupporting
confidence: 92%
“…When looking at the ratio of the patients who experienced adverse effects, the ratio of the participants who experienced the local reactions was 26.0%‐86.0%, 28 and the ratio of the participants who had systemic reactions was 5.0%‐7.0% 29 . In a study consisting of children, 30 the ratio of local reactions was 75.2% and that of systemic reactions was 9.3%. In another study, 18 local, large local, and systemic reactions have been reported in children as 11.9%, 5.0%, and 4.7%, respectively.…”
Section: Discussionmentioning
confidence: 99%